Factors affecting customers’ decision to use a credit card at HDBank Binh Phuoc - Nguyen, Thị Thu Vân; Vu , Cẩm Nhung (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
The study was conducted to explore factors affecting customers’ decision to use a credit card at HDBank Binh Phuoc with a total of six research hypotheses. Using quantitative research methods and convenient sampling methods, the results of data processing using SPSS software showed that 4/6 factors were proven to have a significantly positive impact on customers’ decision to use a credit card at HDBank Binh Phuoc, according to the level of influence from highest to lowest as follows: Responsiveness; Perceived cost; Perceived usefulness; and Attitude. However, the remaining two factors, Perceived trust and Perceived ease of use, were proven to have no significant impact on customers’ decision to use a credit card at HDBank Binh Phuoc.